Effects of N-Acetyl-L-Cysteine on Serum Indices and Hypothalamic AMPK-Related Gene Expression Under Chronic Heat Stress - Li, Zhengqing; Zhao, Yulan; Zhuang, Yu; Xu, Zheng; Wu, Cong; Liu, Ping; Hu, Guoliang; Li, Guyue; Chen, Wei; Gao, Xiaona; Guo, Xiaoquan (Frontiers in Veterinary Science, 2022)
This study aims to investigate the effect of heat stress on the physiological metabolism of young laying hens and whether N-acetyl-l-cysteine (NAC) can effectively alleviate heat stress. 120 Hy-Line Brown laying hens aged 12 weeks were randomly divided into 4 groups: the control group (fed on basal diet under thermal neutral condition), HS group (fed on basal diet under heat stress condition), CN group (fed on the basic meal supplemented with 1000 mg NAC per kg under thermal neutral condition), and HS+N group (fed on the basic meal was supplemented with 1000 mg NAC per kg under heat stress condition). The HS and HS+N groups were exposed to 36±1 ℃ for 10 hours/day. The effects of NAC on the changes of serum concentrations of T3, T4, and CORT and hypothalamic gene and protein expressions induced by heat stress were measured. Results showed that heat stress upregulated the contents of T3, T4, and CORT, while NAC reduced the contents of T3, T4, and CORT. In addition, NAC downregulated AgRP expression, while upregulated the expression of POMC. Moreover, the expressions of AMPKα1, LKB1, and CPT1 were inhibited by NAC, while the expressions of AKT1, ACC, GPAT, and PPARα were increased after NAC treatment, and HMGR did not change significantly. Western blot and comprehensive immunofluorescence section of AMPK in the hypothalamus showed that NAC attenuated the activity of AMPK. In conclusion, NAC can enhance the resistance of laying hens to heat stress by alleviating the metabolic disorders of serum T3, T4, and CORT induced by heat stress, inhibiting the activation of the AMPK pathway and regulating the expression of appetite-related genes in the hypothalamus.